A preliminary study of alcohol use among the male on-campus students in UiTM Sarawak branch Samarahan campus / Pauline Achan ... [et al.] - Achan, Pauline; Jau, Pauline; Clement, Claudius (2003)
This study reports on the preliminary study of alcohol use amongst the male oncampus students in UiTM Sarawak Branch Samarahan Campus. The university assumes a zero tolerance on drinking in the campus, as IS spelt out in the University Act (Act 174). With regard to this, it aims to find out the extent of drinking among the male students who are staying in the hostels. The questionnaire survey method is used to conduct this study, Besides exploring the extent of drinking among the male students in the hostels, it attempts to investigate the reasons and factors that lead them to drink.